2018
DOI: 10.1111/jace.16273
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional Ag/TiO2/reduced graphene oxide with optimal surface‐enhanced Raman scattering and photocatalysis

Abstract: A multifunctional Ag/TiO 2 /reduced graphene oxide (rGO) ternary nanocomposite was prepared by a one-step photochemical reaction with TiO 2 and Ag nanoparticles successively deposited on reduced graphene oxide. The structure, morphology, composition, optical, and photoelectrochemical properties of Ag/TiO 2 /rGO were investigated in detail. Meanwhile, the ternary nanocomposite possessed much higher adsorption capacity to organic dyes compared with bare TiO 2 and binary Ag/TiO 2 , which would help to its use for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The Raman spectrum is one of the most powerful characterization techniques for carbon materials . Figure shows the Raman spectra of the boundary before and after sintering, and the typical Raman spectrum of GO with D peak at 1356 cm −1 and G peak at 1598 cm −1 are depicted (Figure , curve a) . The Raman spectrum of the boundary after sintering showed a 2D peak at 2693 cm −1 except for the D and G peaks (Figure , curve b), thereby indicating three representative characteristic peaks of graphene appeared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raman spectrum is one of the most powerful characterization techniques for carbon materials . Figure shows the Raman spectra of the boundary before and after sintering, and the typical Raman spectrum of GO with D peak at 1356 cm −1 and G peak at 1598 cm −1 are depicted (Figure , curve a) . The Raman spectrum of the boundary after sintering showed a 2D peak at 2693 cm −1 except for the D and G peaks (Figure , curve b), thereby indicating three representative characteristic peaks of graphene appeared.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Figure 3 shows the Raman spectra of the boundary before and after sintering, and the typical Raman spectrum of GO with D peak at 1356 cm −1 and G peak at 1598 cm −1 are depicted ( Figure 3, curve a). 28 The Raman spectrum of the boundary after sintering showed a 2D peak at 2693 cm −1 except for the D and G peaks (Figure 3, curve b), thereby indicating three representative characteristic peaks of graphene appeared. The intensity ratio of the D and G peaks (I D /I G ) was smaller than that of GO, which indicated that part of sp 3 hybridization was converted to sp 2 hybridization.…”
Section: Flexural Strength and Fracture Behavior Testsmentioning
confidence: 96%
“…The size of Ag NPs obtained by photodeposition has been reported to be 5-15 nm. 37 Fig. 3(c) is an SEM image of ZnO nanoparticles xed on FTO glass grown from TiO 2 nanorods by sol-gel method, it can be seen from the image that the ZnO nanoparticles are wrapped around the TiO 2 nanorods.…”
Section: Resultsmentioning
confidence: 99%
“…4(a), the diameter of the surface Ag NPs distributed on the ZnO nanorods is about 10-20 nm, which is in agreement with what has been reported in the literature. 37 This can reect the ZnO nanorods to provide more adhesion area for Ag quantum dots, which will be benecial to the SPR effect of Ag, photoelectrochemical performance and photocatalytic efficiency.…”
Section: (D) Can Be Seen) Tio 2 Nanorodsmentioning
confidence: 99%
“…When studying the catalytic performance of the sample, methyl orange was selected as the target contaminant to explore the PC activity under simulated sunlight. [] The auto‐degradation of contaminants (MO) can be ignored under light conditions. Figure B shows the efficiency of the photodegradation of different samples under UV irradiation.…”
Section: Resultsmentioning
confidence: 99%